ANALYSIS OF A DYNAMIC ELASTO-VISCOPLASTIC FRICTIONLESS ANTIPLAN CONTACT PROBLEM WITH NORMAL COMPLIANCE - OURAHMOUN ABBES (Université de M'sila, 2021)
We consider a mathematical model which describes the dynamic evolution of a thermo elasto viscoplastic contact problem between a body and a rigid foundation. The mechanical and thermal properties of the obstacle coating material near its surface. A variational formulation of this dynamic contact phenomenon is derived in the context of general models of thermo elasto viscoplastic materials. The displacements and temperatures of the bodies in contact are governed by the coupled system consisting of a variational inequality and a parabolic differential equation. The proof is based on a classical existence and uniqueness result on parabolic inequalities,differential equations and fixed point arguments